2020
DOI: 10.3389/fevo.2020.579667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical and Auditory Cues of Hoopoes (Upupa epops) in Repellence and Attraction of Blood-Feeding Flies

Abstract: Research on the mechanisms involved in host location by parasites is of paramount importance and may aid in developing protective measures against them. This topic attains far-reaching repercussions for human and animal welfare regarding parasites transmitting vector-borne pathogens, such as blood-feeding flies. Very few studies have evaluated the effect of bird-derived cues on attraction of vectors in field conditions. We here explored the attraction of different groups of blood-feeding flies (mosquitoes, bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 107 publications
0
19
0
Order By: Relevance
“…Host sounds could potentially be used by other mosquito species to locate their hosts, as suggested for ornithophilic species being attracted to the begging calls of nestlings (Tomás & Soler, 2016). However, the same authors did not find support for this hypothesis when they tested the effect of begging auditory cues of nestling hoopoes ( Upupa epops ) on blood‐feeding flies including mosquitoes (Tomás et al ., 2020). To the best of our knowledge, no evidence to date has suggested that sound plays a role in human location by anthropophilic mosquitoes.…”
Section: Determinants Of Host Utilization By Mosquitoesmentioning
confidence: 99%
“…Host sounds could potentially be used by other mosquito species to locate their hosts, as suggested for ornithophilic species being attracted to the begging calls of nestlings (Tomás & Soler, 2016). However, the same authors did not find support for this hypothesis when they tested the effect of begging auditory cues of nestling hoopoes ( Upupa epops ) on blood‐feeding flies including mosquitoes (Tomás et al ., 2020). To the best of our knowledge, no evidence to date has suggested that sound plays a role in human location by anthropophilic mosquitoes.…”
Section: Determinants Of Host Utilization By Mosquitoesmentioning
confidence: 99%
“…For defense against predator or parasite enemies, some animals use metabolites synthesized by other organisms with antimicrobial and antipredatory properties (i.e., self-medication [ 94 , 109 , 110 , 111 , 112 , 113 ]). Animals also use defensive metabolites that are endogenously produced (e.g., uropygial gland secretions of birds [ 113 , 114 , 115 , 116 , 117 ]).…”
Section: Beneficial Effects Of the Microbiome In Relation To Parasitism And Predationmentioning
confidence: 99%
“…For defense against predator or parasite enemies, some animals use metabolites synthesized by other organisms with antimicrobial and antipredatory properties (i.e., self-medication [ 94 , 109 , 110 , 111 , 112 , 113 ]). Animals also use defensive metabolites that are endogenously produced (e.g., uropygial gland secretions of birds [ 113 , 114 , 115 , 116 , 117 ]). Some of these endogenously produced compounds are volatiles, and abundant correlative and experimental evidence supports the role of such metabolites in interfering with host attractiveness to predators and parasites [ 85 , 118 , 119 , 120 , 121 , 122 ].…”
Section: Beneficial Effects Of the Microbiome In Relation To Parasitism And Predationmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we developed a cross-fostering experiment based on the results obtained and considering that the observed differences between the 2 forests could be due to the effects of habitat type on the emission of nestling cues (e.g. microbiota, Ruiz-López, 2020; or the composition of uropygial secretions, Tomás et al, 2020), rather than a direct association between habitat type and Culicoides. This study design meant we could examine the role of rearing environment conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%